AN OVERVIEW OF MULTIPLE SCLEROSIS WITH GUT EPSILON TOXICITY IN HUMAN: SISTEMATIC LITERATURE REVIEW: MULTIPLE SCLEROSIS WITH GUT EPSILON TOXICITY - MOHAMMAD SALIM; Shagufta Parween; Mohammad Shahid Masroor (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Multiple Sclerosis (MS) is a complex autoimmune neurodegenerative disorder that afflicts a significant number of individuals worldwide. This formidable disease, which is often life-threatening, imposes a lifelong impact on those diagnosed, altering their existence in profound ways. Methods: The current review is meticulously crafted, drawing upon a multitude of scholarly articles previously disseminated in both national and international academic journals within the same discipline. Results: This disease inflicts substantial damage to the Central Nervous System (CNS), predominantly affecting the myelin sheath of nerve fibers, spinal cord, and eyes, thereby leading to the development of muscle weakness, movement disorders, and visual impairments. Recent observations have unveiled a potential link between a gut bacterium, Clostridium perfringens, and the onset of MS in humans. Conclusion: Given that the precise etiology of Multiple Sclerosis (MS) remains elusive and presents a formidable challenge, this paper endeavors to shed light on the current landscape of the disease. It provides an in-depth exploration of its epidemiology, clinical manifestations, diagnostic procedures, prognosis, and treatment modalities, all underpinned by the most recent advancements in the fields of immunology and medical microbiology about infectious diseases.